2017
DOI: 10.48550/arxiv.1706.05806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SVCCA: Singular Vector Canonical Correlation Analysis for Deep Learning Dynamics and Interpretability

Abstract: We propose a new technique, Singular Vector Canonical Correlation Analysis (SVCCA), a tool for quickly comparing two representations in a way that is both invariant to affine transform (allowing comparison between different layers and networks) and fast to compute (allowing more comparisons to be calculated than with previous methods). We deploy this tool to measure the intrinsic dimensionality of layers, showing in some cases needless over-parameterization; to probe learning dynamics throughout training, find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 13 publications
0
28
1
Order By: Relevance
“…In both of the experimental settings there is a one-to-one correspondence between points in the point clouds. We compared these point clouds by calculating: RTD (proposed), CKA (Kornblith et al, 2019), IMD (Tsitsulin et al, 2020) and SVCCA (Raghu et al, 2017). We calculated linear CKA since (Kornblith et al, 2019) concluded that it provides the same performance as with RBF kernel but doesn't require to select a kernel width.…”
Section: Experiments With Synthetic Point Cloudsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both of the experimental settings there is a one-to-one correspondence between points in the point clouds. We compared these point clouds by calculating: RTD (proposed), CKA (Kornblith et al, 2019), IMD (Tsitsulin et al, 2020) and SVCCA (Raghu et al, 2017). We calculated linear CKA since (Kornblith et al, 2019) concluded that it provides the same performance as with RBF kernel but doesn't require to select a kernel width.…”
Section: Experiments With Synthetic Point Cloudsmentioning
confidence: 99%
“…We calculated linear CKA since (Kornblith et al, 2019) concluded that it provides the same performance as with RBF kernel but doesn't require to select a kernel width. For SVCCA, we calculated average correlation ρ for the truncation threshold 0.99, as recommended by the authors (Raghu et al, 2017). The IMD score (Tsitsulin et al, 2020) was very noisy and we averaged it over 100 runs.…”
Section: Experiments With Synthetic Point Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one approach is to investigate what certain units are looking for by generating artificial inputs that maximizes an individual neuron's activation (Erhan et al, 2009). Alternatively, it is possible to study the activations of each neuron after passing certain data through the model, whose results can reflect on the input data and allows for further unsupervised investigation (Simonyan et al, 2013;Raghu et al, 2017).…”
Section: Representation Analysismentioning
confidence: 99%
“…Raghu et al [30] proposed Singular Vector Canonical Correlation Analysis (SVCCA) for comparing two representations. They defined a neuron as a vector in R m over a dataset with m examples.…”
Section: Similarity Indexmentioning
confidence: 99%